2006
DOI: 10.1097/01.aog.0000202401.29145.68
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Atypical Glandular Cells on Cervical Cytology

Abstract: Histologic diagnosis showed that 29.0% of these Pap tests had findings requiring follow-up or therapeutic intervention, including a 5.2% rate of malignancy. Based on these findings, 99.6% of the diagnoses are within the region of surveillance when AGUS Pap tests are evaluated with colposcopy and directed biopsy, endocervical curettage, an endometrial biopsy in patients with risk factors for endometrial cancer, and pelvic examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
118
2
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(147 citation statements)
references
References 34 publications
18
118
2
8
Order By: Relevance
“…9 Several studies have demonstrated that AEC may be associated with premalignant or malignant cervical lesions but most have been limited by short follow-up periods and/or relatively small numbers of cases. 7,[10][11][12] Furthermore, the risk of significant pathology has not always been correlated with age, prior smear history, presence of endocervical cells in preceding cytology samples or the socio-economic status of the patient. In the present study, we have investigated the potential relationship between these factors and the risk of high-grade cervical dysplasia and gynaecological malignancies in women with a cytological diagnosis of AEC in Western Australia (WA) over a seven-year period.…”
Section: Introductionmentioning
confidence: 99%
“…9 Several studies have demonstrated that AEC may be associated with premalignant or malignant cervical lesions but most have been limited by short follow-up periods and/or relatively small numbers of cases. 7,[10][11][12] Furthermore, the risk of significant pathology has not always been correlated with age, prior smear history, presence of endocervical cells in preceding cytology samples or the socio-economic status of the patient. In the present study, we have investigated the potential relationship between these factors and the risk of high-grade cervical dysplasia and gynaecological malignancies in women with a cytological diagnosis of AEC in Western Australia (WA) over a seven-year period.…”
Section: Introductionmentioning
confidence: 99%
“…Among benign or reactive changes are included endocervical and endometrial polyps, tubal metaplasia, cervical endometriosis, microglandular hyperplasia, genital tract inflammatory changes, and direct sampling of the lower uterine segment cells. On the other hand, it may also represent/correspond to squamous and glandular cervical lesions (malignant and pre-malignant), endometrial hyperplasia, invasive endometrial adenocarcinoma, and extra-uterine tumor (tubal, ovarian, and bowel), among others (2,3,11,12) . ACG are divided in two groups, according to their estimated significance: "possibly non-neoplastic" or "cannot exclude highgrade intraepithelial lesion", as the Nomenclatura Brasileira para Laudos de Colpocitologia (Brazilian Nomenclature for Cervical Cytology Reporting).…”
Section: Introductionmentioning
confidence: 99%
“…Although our HPV-DNA testing sample was small in size we found a ratio of HPV associated cervical disease of 50% which indicates that the concomitant use of HPV-DNA can be very useful on AGC followup when no significant pathology is found on cervix or endometrium since studies report a false negative rate of 4.7% in AGC follow-up [6].…”
Section: Discussionmentioning
confidence: 71%
“…Whereas these used to account for less than 5% of all cervical cancers, they now comprise 20% to 25% [4]. One of the main reasons for the increasing relative rate of adenocarcinomas seems to be the lower Pap sensitivity in diagnosing glandular lesions and a high false negative rate [5,6]. Glandular abnormalities are found in 0.1 to 2.1% of Pap tests being more frequent in women over 40 [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation